Voltage-Sensor Transitions of the Inward-Rectifying K+ Channel KAT1 Indicate a Latching Mechanism Biased by Hydration within the Voltage Sensor . Issue 2 (2nd September 2014) - Lefoulon, Cécile; Karnik, Rucha; Honsbein, Annegret; Gutla, Paul Vijay; Grefen, Christopher; Riedelsberger, Janin; Poblete, Tomás; Dreyer, Ingo; Gonzalez, Wendy; Blatt, Michael R.
Abstract : Manipulating the electrostatic charge network that stabilizes the voltage sensor of the KAT1 K + channel displaces channel gating across more than 140 mV within the physiological voltage range . Abstract: The Kv-like (potassium voltage-dependent) K + channels at the plasma membrane, including the inward-rectifying KAT1 K + channel of Arabidopsis ( Arabidopsis thaliana ), are important targets for manipulating K + homeostasis in plants. Gating modification, especially, has been identified as a promising means by which to engineer plants with improved characteristics in mineral and water use. Understanding plant K + channel gating poses several challenges, despite many similarities to that of mammalian Kv and Shaker channel models. We have used site-directed mutagenesis to explore residues that are thought to form two electrostatic countercharge centers on either side of a conserved phenylalanine (Phe) residue within the S2 and S3 α-helices of the voltage sensor domain (VSD ) of Kv channels. Consistent with molecular dynamic simulations of KAT1, we show that the voltage dependence of the channel gate is highly sensitive to manipulations affecting these residues. Mutations of the central Phe residue favored the closed KAT1 channel, whereas mutations affecting the countercharge centers favored the open channel. Modeling of the macroscopic current kinetics also highlighted a substantial difference between the two sets of mutations. We interpret these findings in the context of the effects on hydration of amino acid residues within the VSD and with an inherent bias of the VSD, when hydrated around a central Phe residue, to the closed state of the channel.